A new diamido-amine ligand based on three-carbon atom "arms": synthesis, structures and polymerisation capability of zirconium derivatives of MeN(CH2CH2CH2NSiMe3)2. - Lowes, T; Ward, B; Whannel, R; Dubberley, SR; Mountford, P (2005)
Zirconium compounds of the new diamido-amine ligand MeN(CH(2)CH(2)CH(2)NSiMe(3))(2) feature significantly different molecular structures and considerably improved olefin polymerisation characteristics in comparison with analogous compounds based on the two-carbon arm homologues.